Fetal outcome and mode of delivery in a patient with meconium-stained amniotic fluid - Rana, Bindra Bharatsinh; Airao, Bhavesh B. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Meconium-stained amniotic fluid (MSAF), especially observed before term, is considered a sign of meconium fetal jeopardy. Methods: All data were retrieved from pregnant patients with MSAF who delivered at OBGY department of C. U. Shah medical college and hospital from February 2022 to July 2022. Results: In this study meconium-stained liquor was more common in primigravida within the age group of 21-30 years of age with moderate type of meconium being more common. Conclusions: In this study we concluded that meconium-stained liquor more commonly seen in primigravida which have associated risk factors like preeclampsia, malposition, prolonged labour and abnormal uterine inertia. It was also reconfirmed that MSAF is associated with a new-born risk, especially meconium aspiration syndrome. Patients had a higher rate for emergent caesarean section and baby admission to NICU. These data may be useful to make health/reproductive-health progress in area.